PENDEKATAN DAN PENILAIAN PEMBELAJARAN PADA KURIKULUM 2013 REVISI 2017 YANG MENDUKUNG PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA - Anisa Astra Jingga; Mardiyana Mardiyana; Triyanto Triyanto (Jurnal Pembelajaran Matematika, 2018)
Abstract: Mathematical connection ability is an ability that becomes the goal of mathematics learning. The importance of mathematical connection ability for students requires teachers to carry out mathematical connection ability in learning and it should be in accordance with the applicable curriculum. The fundamental difference between curriculum 2013 and the previous curriculum lies in the learning approach and learning assessment. This is a library research which combines all relevant books, journals, and other libraries as data sources. The purpose of this study is to find out how 2013 curriculum supports the improvement of students' mathematical connection ability. The scientific approach contains observing and gathering information activities. The RME approach contains the implementation of characters, such as the real world context, models, production, students’ construction, interaction, and interrelatedness. The CTL approach contains components in the form of making meaningful connection and doing significant work. AfL consists of feedback activities. AaL contains self-analysis, self-reference, self-evaluation, self-correction performed by students in the learning process, and other metacognitive strategies. These things facilitate students and teachers to develop mathematical connection ability.Keywords: AaL, AfL, Mathematical Connection, Approach.